Eukaryotic diversity patterns in the Red Sea: from the surface to the deep - Pearman, John K.; Jones, Burton; Qashqari, Maryam; Carvalho, Susana (Frontiers in Marine Science, 2024)
Understanding how biological communities are assembled is central to many ecological studies. The semi-confined nature of the Red Sea, with limited exchange of waters with other seas and strong environmental gradients, is an ideal ecosystem to investigate assembly processes of biological communities. Sampling through the water column (surface, deep chlorophyll maximum (DCM), oxygen minimum zone (OMZ), and bottom) along the latitudinal axis of the Red Sea was undertaken during cruises in 2015/2016. The composition and assembly of eukaryotic communities were assessed using high-throughput sequencing of the 18S rRNA gene. Distinct differences were noted in the composition of the eukaryotic community across the different depth layers. Dinophyceae were more prevalent in the euphotic zone (surface = 35.3%; DCM = 18.1%), while Syndiniales had the highest relative abundances in the OMZ (45.9%) and the bottom waters (52.6%). We showed that the assembly of eukaryotic communities through the water column was primarily determined by deterministic processes, especially variable selection due to different environmental conditions. The exception was between the OMZ and the bottom, where deterministic and stochastic processes were balanced with homogeneous selection and homogenizing dispersal dominating, indicating similar environmental conditions and high levels of dispersal between the layers. Across the latitudinal gradient, environmental variable selection was predominant in the euphotic zone, most likely driven by the strong environmental gradients present in the Red Sea. In the aphotic zones, homogenizing dispersal was more prevalent, especially in the OMZ. Our study highlights the contrasting assembly mechanisms governing the distribution of eukaryotic planktonic communities through the water column.